Developing the academic literacy of undergraduates studying by distance education in South Africa - Collet, Philip Godfrey (University of the Free State, 2002)
This research has been conducted at a time of major transformation in higher education, both in South Africa and internationally, which involves the re-engineering of education processes, such as content delivery, assessment and learner support, in order to meet the needs of lifelong learning in an information society. Distance education, as an important component of South African higher education, is a key to this transformation due to the convergence of traditional and more open and flexible forms of higher education and as such needs to respond to multiple challenges of enabling access to growing numbers of non-traditional higher education students; improving teaching and learning; implementing new information and communications technologies; articulating with new qualifications and quality assurance frameworks; and rationalising and optimising available institutional resources to respond to these challenges. A review of the fields of distance education and academic literacy revealed that older 'transmission' type paradigms, epitomised by content based correspondence education in which the distance learner absorbs theoretical knowledge in isolation, are inimical to the development of academic literacy. Academic literacy is understood as that complex of knowledge, attitudes. and values which allows meaningful and successful participation of the student in the academic culture and, more broadly, in developing personal and professional competencies which equip the student for productive involvement in the society at a high level. Constructivist orientations to learning are generally considered to facilitate meaningful development of academic literacy. This study aimed to: } Illuminate the development of academic literacy in students studying undergraduate courses through distance education in South African higher education; } Identify and describe effective practice of distance education institutions, and effective learning behaviours of the learners themselves, in facilitating the development of academic literacy; ~ Identify and describe problem areas in the development of academic literacy in undergraduate distance learners; ~ Recommend improvements in practice and further research to facilitate the development of academic literacy in distance education. A mix of empirical and theoretical methods was used in a cycle of deductive and inductive research to pursue these aims. Data was gathered using postal and e-mail questionnaires to distance learners and lecturers and this was supplemented by interviews. The most important findings emerging from the study are: ~ Transmission models of teaching and learning are still very much in evidence, although some innovation is taking place in the areas of support, communication and materials development; ~ For many distance learners there is a critical lack of engagement with lecturers and with fellow students which precludes meaningful development of academic literacy; ~ For the most disadvantaged students, access to sufficient learning support, a prerequisite for academic literacy development, is problematic. Major conclusions drawn from the study include the following: ~ Innovations in support, communication and materials developments need to be implemented more quickly if a significant number of students are to benefit; ~ A critical threshold of involvement in the process of developing academic literacy, by means of constructive learning in a range of contexts, needs to be established in order to ensure acceptable learning outcomes in South African distance education; ~ Learner support structures need to be made available to the majority of students to ensure equity, student retention and mission achievement; ~ Sustained research by institutions of learner support needs, learning dynamics, and experience of services is vital to the successful adaptation of the sector.

Hierdie navorsing is gedoen in 'n tyd van belangrike transformasie in hoëronderwys - beide in Suid-Afrika en op internasionale vlak; 'n transformasie wat die heropbou van opvoedkundige prosesse soos die oordrag van inhoud, assessering en ondersteuning vir studente, met die doel om behoeftes van lewenslange leer in 'n inligtingsgemeenskap aan te spreek, behels. Weens die sameloop van tradisionele hoëronderwyspatrone en ope leer, meer plooibare benaderings, is 'n belangrike komponent van die hoëronderwysstelsel in Suid-Afrika, naamlik afstandsonderrig, 'n sleutel tot transformasie. Dit is noodsaaklik dat transformasie aan veelvuldige uitdagings gehoor moet gee: verbeterde toegang van groeiende getalle nie-tradisionele studente in hoëronderwys; vernuwing van maniere waarop kennis oorgedra en ontvang word; die inwerkingstelling van nuwe inligtings- en kommunikasietegnologieë; aansluiting by nuwe raamwerke vir kwalifikasies en gehalteversekering, en die rasionalisering en optimale benutting van beskikbare institusionele hulpbronne. 'n Oorsig van die vakgebiede in afstandsonderrig en akademiese geletterdheid onthul dat vroeë tipes "sender"- paradigmas, gekenmerk deur inhoudsgebaseerde korrespondensiekursusse waardeur die afstandstudent in isolasie teoretiese kennis opdoen, strydig is met die ontwikkeling van akademiese geletterdheid. Dit word algemeen aanvaar dat akademiese geletterdheid 'n samestelling is van kennis, houdings en waardes wat die student in staat stelom sinvol en produktief by die akademiese kultuur aan te sluit én algemene persoonlike en professionele bevoegdhede te ontwikkel wat vrugbare maatskaplike betrokkenheid op gevorderde vlak in die hand werk. Dit word algemeen aanvaar dat konstruktiwistiese benaderings tot die leerproses die sinvolle ontwikkeling van akademiese geletterdheid tot gevolg het. Hierdie studie se mikpunte was die: ~ Beligting van die ontwikkeling van akademiese geletterdheid onder studente wat voorgraadse kursusse deur afstandsonderrig in die Suid-Afrikaanse hoëronderwysstelsel volg; >- Identifisering en beskrywing van effektiewe praktyke by instellings wat afstands-onderrig aanbied en die doeltreffende leergewoontes van leerders met die doelom akademiese geletterdheid te fasiliteer; >- Indentifisering en beskrywing van probleemareas in die ontwikkeling van akademiese geletterdheid onder voorgraadse studente wat afstandsonderrig ontvang; >- Maak van aanbevelings ter verbetering van praktyke en die voorstel van verdere navorsing wat die ontwikkeling van akademiese geletterdheid in afstandsonderrig kan fasiliteer. 'n Verweefdheid van empiriese en teoreties metodes in 'n siklus van deduktiewe en induktiewe navorsing is aangewend in 'n poging om die mikpunte van hierdie studie te bereik. Die studie se belangrikste bevindings is soos volg: » Transmissie-modelle van onderwys word nog dikwels gebruik ofskoon 'n mate van vernuwing ten opsigte van ondersteuning, kommunikasie en die ontwikkeling van leerstof wel plaasvind; >- Baie afstandleerders ervaar 'n kritieke gebrek aan verbintenis met dosente en medestudente wat die betekenisvolle ontwikkeling van akademiese geletterdheid uitskakel; >- Die meeste minderbevoorregte studente kry moeilik toegang tot voldoende ondersteuningstelsels wat uiteraard 'n voorvereiste is vir die ontwikkeling van akademiese geletterdheid. Die belangrikste gevolgtrekkings wat uit hierdie studie na vore kom is: » Vernuwing in ondersteuningstelsels. kommunikasie en die ontwikkeling van leerstof sal vinniger moet geskied indien 'n beduidende getal studente voordeel daaruit moet trek; >- 'n Kritieke drempel van betrokkenheid by die ontwikkeling van akademiese geletterdheid deur middel van konstruktiewe leerprosesse in 'n verskeidenheid van kontekste is noodsaaklik vir aanvaarbare leeruitkomstes in Suid-Afrikaanse afstandsonderrig; » Ondersteuningstrukture moet aan die meerderheid studente beskikbaar gestel word om billikheid, die behoud van studente-getalle en missievervulling te verseker; );> Volgehoue formele navorsing oor studente se ondersteuningsbehoeftes, die dinamiese aard van kennisopname en ervarings van dienslewering is van kardinale belang vir die geslaagde aanpassing van die hoëronderwyssektor.
Thesis (Ph.D. (Higher Education))--University of the Free State, 2002
Keywords: Academic literacies; Distance education; Open learning; Independent learning; Higher Education; Undergraduate education; Illuminative evaluation; Cognitive skills; Learner support; On-line learning; Reading (Adult education); Literacy programs -- South Africa; Distance education -- South Africa